2001
DOI: 10.1523/jneurosci.21-07-02373.2001
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Guidance of Olfactory Bulb Axons Is Independent of Repulsive Factor Slit

Abstract: During development, mitral cells, the major output neurons of the olfactory bulb, project their axons caudolaterally into the telencephalon and form the lateral olfactory tract (LOT). Two types of guidance cues have been suggested for this projection. First, a long-range factor Slit, which is secreted from the septum, repels mitral cell axons into a caudolateral direction. Second, the pathway of mitral cell axons contains a subset of neurons designated as lot cells, which guide the axons through short-range in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
0
20
0
4
Order By: Relevance
“…Thus, the removal of the septum or the addition of a Robo1 ectodomain in whole-telencephalon organotypic cultures did not affect the projection of mitral cell axons (Hirata et al, 2001). Our results demonstrate that the distribution of lot1-expressing cells is not significantly perturbed in Slit1-, Slit2-, Slit1;Slit2-, or Robo1-, Robo2-and Robo1;Robo2-deficient mice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the removal of the septum or the addition of a Robo1 ectodomain in whole-telencephalon organotypic cultures did not affect the projection of mitral cell axons (Hirata et al, 2001). Our results demonstrate that the distribution of lot1-expressing cells is not significantly perturbed in Slit1-, Slit2-, Slit1;Slit2-, or Robo1-, Robo2-and Robo1;Robo2-deficient mice.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown previously that LOT axons may be guided through short-range interaction with so-called "lot cells," which may act as guidepost cells (Hirata et al, 2001). Lot cells can be visualized with the monoclonal antibody mAb lot1 and migrate ventrally from the dorsal telencephalic vesicle to their final position (Sato et al, 1998;Tomioka et al, 2000).…”
Section: Robo-deficient Micementioning
confidence: 99%
“…16 Such cells have been identi®ed by the mAb lot1 as a subset of early-generated neurons formed exclusively in the neocortex, which migrate to reach their position in the basal telencephalon, thereby enclosing the LOT area. 68,69 These lot1-positive cells may produce factors that either attract or support axonal outgrowth. Indeed, lot1-positive cells seem to form a border in most areas of the olfactory cortex, beyond which LOT axons do not grow.…”
Section: Cell Death and Differentiationmentioning
confidence: 99%
“…72,73 However, Slit-2 may not play a simple role in this process. 36,69 Recently, the group of Pini suggested that a concurrent cue may also exist that is responsible for the repellent activity of the septum and that which may be different from Slit-2 (see Figure 2). 74 LOT axons also respond selectively to the secreted semaphorins.…”
Section: Cell Death and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation